Mesenchymal Stem Cell-Derived Neuron-Like Cell Transplantation Combined with Electroacupuncture Improves Synaptic Plasticity in Rats with Intracerebral Hemorrhage via mTOR/p70S6K Signaling. (15th February 2022) - Yang, Guoqiang; Zhu, Jiayi; Zhan, Guwen; Fan, Guangbi; Deng, Li; Tang, Huajun; Jiang, Xiaoqian; Chen, Bo; Yang, Chaoxian
Abstract : Previous studies have shown that the combination of mesenchymal stem cell (MSC) transplantation and electroacupuncture (EA) stimulation is a neuroprotective strategy for treating intracerebral hemorrhage (ICH). However, the underlying mechanisms by which the combined treatment promotes neuroprotection remain unclear. This study was designed to investigate the effects of the combined treatment on synaptic plasticity and elucidate their underlying mechanisms. Therefore, rat ICH models were established by injecting collagenase and heparin, and the animals were randomly divided into model control (MC), EA stimulation (EA), MSC-derived neuron-like cell transplantation (MSC-dNLCs), and MSC-dNLC transplantation combined with EA stimulation (MSC-dNLCs+EA) groups. We observed the ultrastructure of the brain and measured the brain water content (BWC) and the levels of the microtubule-associated protein 2 (MAP2), galactocerebrosidase (GALC), and glial fibrillary acidic protein (GFAP) proteins. We also measured the levels of the phosphorylated mammalian target of rapamycin (mTOR) and 70 kDa ribosomal protein S6 kinase (p70S6K) proteins, as well as the expression of synapse-related proteins. The BWC increased in rats after ICH and decreased significantly in ICH rats treated with MSC-dNLC transplantation, EA stimulation, or combined therapy. Meanwhile, after ICH, the number of blood vessels increased more evidently, but only the combined treatment reduced the number of blood vessels among rats receiving the three treatments. Moreover, the levels of MAP2, GALC, postsynaptic density 95 (PSD95), and synaptophysin (SYP) proteins, as well as the levels of the phosphorylated mTOR and p70S6k proteins, increased in the MSC-dNLCs+EA group compared with those in the MSC-dNLCs and EA groups. Compared with the MC group, GFAP expression was significantly reduced in the MSC-dNLCs, EA, and MSC-dNLCs+EA groups, but the differences among the three treatment groups were not significant. In addition, the number of synapses increased only in the MSC-dNLCs+EA group compared to the MC group. Based on these data, the combination of MSC-dNLC transplantation and EA stimulation exerts a synergistic effect on improving the consequences of ICH by relieving cerebral edema and glial scarring, promoting the survival of neurons and oligodendrocytes, and activating mTOR/p70S6K signaling to enhance synaptic plasticity.